2022
DOI: 10.3390/rheumato2010003
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme Activity May Predict Disease Severity in Psoriasis

Abstract: Psoriasis is a multifactorial disease, with many genetic risk factors, one of which seems to be the angiotensin-converting enzyme (ACE) insertion/deletion (I/D) polymorphism. ACE activity has been shown to be higher in psoriatic patients and it suggests an oxidative stress state, as seen in many cardiovascular disorders. We aimed to explore the association between ACE activity and polymorphisms and cardiovascular risk amongst psoriatic patients. We included 64 psoriatic patients and 1091 controls and compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Besides, ACE activity potentially predicts the severity of PsD, independent of ACE I/D polymorphism genotype. In comparison with control group, the psoriatic patients show higher serum levels of ACE that associates with lipid profile modulation, reflecting an increased stress oxidative status as an underlying risk factor in cardiovascular disorders 72 . Despite disease severity and family history, the results of a meta-analysis also revealed that ID and DD genotypes may serve a protective role against psoriatic arthritis, particularly in Caucasian patients 73 .…”
Section: Angiotensin-converting Enzyme (Ace) Inhibitorsmentioning
confidence: 89%
See 1 more Smart Citation
“…Besides, ACE activity potentially predicts the severity of PsD, independent of ACE I/D polymorphism genotype. In comparison with control group, the psoriatic patients show higher serum levels of ACE that associates with lipid profile modulation, reflecting an increased stress oxidative status as an underlying risk factor in cardiovascular disorders 72 . Despite disease severity and family history, the results of a meta-analysis also revealed that ID and DD genotypes may serve a protective role against psoriatic arthritis, particularly in Caucasian patients 73 .…”
Section: Angiotensin-converting Enzyme (Ace) Inhibitorsmentioning
confidence: 89%
“…Besides, ACE activity have potential to predict the PsD severity, independent of ACE I/D polymorphism genotype. In the clinical settings, the psoriatic patients showed higher serum levels of ACE that had association with lipid profile modulation, reflecting an increased stress oxidative status, as an underlying risk factor in CVD 72 .…”
Section: Discussionmentioning
confidence: 99%
“…The imbalanced ACE/ACE2 ratio seen in psoriasis, with higher ACE tissue concentrations and activity as well as a tendency for higher ACE serum levels, correlates with higher CV comorbidity [ 14 , 15 ] . On the other hand, binding of the virus to ACE2 can result in ACE2 downregulation, which could lead to excessive production of angiotensin by the ACE enzyme, the opposing physiological homologue of ACE2.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory testing in rheumatic diseases received attention, first from Rothschild [1], addressing the importance of crystal recognition for the diagnosis of gout, and additionally from the team of Bandeira, Gil, Santos, Romão, Mascarenhas, Filipe, Fonseca and Bicho [6], specifically examining a role of angiotensin-converting enzyme (ACE) activity and its genetics as a factor in predicting the severity of psoriasis.…”
mentioning
confidence: 99%